COPA syndrome in an Icelandic family caused by a recurrent missense mutation in COPA - Brynjar O. Jensson; Sif Hansdottir; Gudny A. Arnadottir; Gerald Sulem; Ragnar P. Kristjansson; Asmundur Oddsson; Stefania Benonisdottir; Hakon Jonsson; Agnar Helgason; Jona Saemundsdottir; Olafur T. Magnusson; Gisli Masson; et al. (BMC, 2017)
Abstract Background Rare missense mutations in the gene encoding coatomer subunit alpha (COPA) have recently been shown to cause autoimmune interstitial lung, joint and kidney disease, also known as COPA syndrome, under a dominant mode of inheritance. Case presentation Here we describe an Icelandic family with three affected individuals over two generations with a rare clinical presentation of lung and joint disease and a histological diagnosis of follicular bronchiolitis. We performed whole-genome sequencing (WGS) of the three affected as well as three unaffected members of the family, and searched for rare genotypes associated with disease using 30,067 sequenced Icelanders as a reference population. We assessed all coding and splicing variants, prioritizing variants in genes known to cause interstitial lung disease. We detected a heterozygous missense mutation, p.Glu241Lys, in the COPA gene, private to the affected family members. The mutation occurred de novo in the paternal germline of the index case and was absent from 30,067 Icelandic genomes and 141,353 individuals from the genome Aggregation Database (gnomAD). The mutation occurs within the conserved and functionally important WD40 domain of the COPA protein. Conclusions This is the second report of the p.Glu241Lys mutation in COPA, indicating the recurrent nature of the mutation. The mutation was reported to co-segregate with COPA syndrome in a large family from the USA with five affected members, and classified as pathogenic. The two separate occurrences of the p.Glu241Lys mutation in cases and its absence from a large number of sequenced genomes confirms its role in the pathogenesis of the COPA syndrome.